Marmoutier (Tours) : de l’hôtellerie médiévale à la maison du Grand Prieur - Élisabeth Lorans; Émeline Marot; Gaël Simon (Bulletin du Centre d’Études Médiévales d’Auxerre)
The monastery of Marmoutier, a large benedictine abbey situated between the hillside and the Loire river, opposite the city of Tours, has been the subject of a major archaeological research programme since 2005. The floor space of the old monastic guest house, of which around a third is still above ground, was excavated between 2006 and 2013, showing a complex evolution of the monastic buildings between the 10th-11th and the 19th centuries. Replacing two buildings likely to have been used as hostelries, we have a new construction dated to the end of the 12th century, to be identified with the guest house for high-ranking visitors said to have been built by Hervé de Villepreux in the Chronicle of the abbots of Marmoutier. This fifty-meters’ long construction is made up of a vaulted ground floor, and a large timber-framed hall. This paper sets out the succession of buildings on the site, and the medieval and modern transformations of the guest house, and proposes a few comparative interpretations.